2011
DOI: 10.1111/j.1365-2559.2011.03964.x
|View full text |Cite
|
Sign up to set email alerts
|

Histopathological predictors of regional lymph node metastasis at the invasive front in early colorectal cancer

Abstract: LN metastasis is regulated not only by the characteristics of cancer cells but also by microenvironmental factors of lymphatics and neutrophils, especially at the invasive front.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
49
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(50 citation statements)
references
References 33 publications
1
49
0
Order By: Relevance
“…However, more recent reports suggest that ANGPTL4 may be proangiogenic and provascular permeability (23,25,(42)(43)(44)(45)(46). ANGPTL4 has been shown to disrupt vascular endothelial cellcell (tight and adherens) junctions, facilitating cellular transendothelial passage and tumor dissemination (47).…”
Section: Discussionmentioning
confidence: 99%
“…However, more recent reports suggest that ANGPTL4 may be proangiogenic and provascular permeability (23,25,(42)(43)(44)(45)(46). ANGPTL4 has been shown to disrupt vascular endothelial cellcell (tight and adherens) junctions, facilitating cellular transendothelial passage and tumor dissemination (47).…”
Section: Discussionmentioning
confidence: 99%
“…The importance of evaluating the invasive front has been reported in several gastrointestinal malignancies [28][29][30][31]. In the present study, we examined RacGAP1 expression at the invasive front in gastric cancer and observed the association of its expression with tumor progression and poor prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…Although several CRC studies have described the overexpression of MMP7 (Akishima-Fukasawa et al, 2011;Karamitopoulou et al, 2011;Nastase et al, 2011;Bujanda et al, 2013), a relationship between the MMP7-181A/G polymorphism and MMP7 overexpression in CRC patients remains to be verified.…”
Section: Association Analysismentioning
confidence: 97%